Luo Tong Formula Alleviates Diabetic Retinopathy in Rats Through Micro-200b Target - Pang, Bing; Ni, Qing; Di, Sha; Du, Li-juan; Qin, Ya-li; Li, Qing-wei; Li, Min; Tong, Xiao-lin (Frontiers in Pharmacology, 2020)
Introduction: Diabetic retinopathy (DR) is a serious microvascular complication of diabetes and remains the leading cause of blindness in adults. Endothelial dysfunction and vascular leakage are important pathological characteristics of early DR. MicroRNA-200b (miR-200b) is closely associated with the development of DR and may regulate vascular endothelial growth factor (VEGF), VEGF receptor (VEGFR), and pigment epithelium-derived factor (PEDF) expression. Additionally, miR-200b is closely related to angiopoietin-1 (Ang-1)/tyrosine protein kinase receptor (Tie-2) expression. Here, we investigated the effects of Luo Tong formula (LTF) on DR in rats and explored the related molecular mechanisms. Methods: Sprague-Dawley rats were divided into four groups: control, streptozotocin-induced diabetic, and LTF-treated diabetic, and calcium dobesilate (CaD)-treated diabetic groups. Blood samples were collected for blood glucose and hemorheology analysis. Hematoxylin-eosin and periodic acid-Schiff staining were conducted for light microscopy observations. Electroretinography (ERG) was assessed the retinal function. Blood retinal-barrier (BRB) breakdown was measured using Evans blue. Claudin-5and Occludin expression levels were evaluated by immunohistochemistry. VEGF, VEGFR, PEDF, Ang-1, Tie-2, ZO-1, Occludin, and Claudin-5 expression levels were evaluated by western blotting and/or real-time polymerase chain reaction (PCR). miR-200b expression was evaluated by quantitative real-time PCR. Results: Diabetic rats showed significant decreases in miR-200b, PEDF, Ang-1, Tie-2, ZO-1, Occludin, and Claudin-5 expression and increases in VEGF and VEGFR expression in the retina compared with those in the normal control group. BRB breakdown was also observed in diabetic rats. LTF treatment significantly improved some histopathological outcomes and hemorrheological parameters, and restored retina function in diabetic rats; decreased BRB leakage and VEGF expression; increased PEDF, ZO-1, Occludin, Ang-1, and Tie-2 expression; and increased retinal miR-200b expression compared with those in diabetic rats. Conclusions: LTF treatment ameliorated DR by affecting vascular endothelial function and attenuating vascular leakage effects. A mechanism involving miR-200b may contribute to the benefits of LTF treatment in DR.